Огляд аспектів застосування ігрових технологій для створення візуальної новели - Зіноватна, Д. В.; Колендовська, М. М. (ХНУРЕ, 2022)
This paper presents the classification of game genres, classification of game mechanics, detailed analysis of systems for creating graphic elements, detailed analysis of engines for creating games, review of methods for creating game scenes, description of functional requirements, developed graphical application interface, developed algorithm for dialogue.